Chlorinated wash water and pH regulators affect chlorine gas emission and disinfection by-products. (December 2020) - Marín, Alicia; Tudela, Juan A.; Garrido, Yolanda; Albolafio, Sofía; Hernández, Natalia; Andújar, Silvia; Allende, Ana; Gil, Maria I.
Abstract: In the washing operations of fruit and vegetables, the maintenance of an appropriate range of pH in the water when using chlorine is crucial to ensure the maximum concentration of hypochlorous acid (HOCl), the form of chlorine with the highest antimicrobial activity. In this study, the effect of two inorganic acids (phosphoric and sulfuric) and two organic acids (carbonic and citric) as pH regulators was evaluated. Chlorinated wash water was generated using sodium hypochlorite as a chlorine source. The results showed that the optimal pH range with >90% of chlorine as HOCl was between 5.0 and 6.0 for all pH regulators. Phosphoric acid and sulfuric acid provided a wider pH range (3.0–6.0) for the maximum HOCl concentration than citric acid and carbonic acid (4.5–6.0 and 5.0–6.0, respectively). When citric acid was used as a pH regulator, a reduction of available chlorine was observed at pH < 4.5, decreasing 50% the concentration at pH 4.0. The implication of citric acid on chlorine gas emission was studied by the changes in free chlorine, comparing citric and phosphoric acids at pH 3.5 and 5.0. These analyses confirmed the emission of gaseous chlorine as after 15 min free chlorine decreased at pH 3.5, while the level was maintained at pH 5.0. Further experiments were conducted to assess the effect of these pH regulators on the generation of disinfection by-products (DBPs), including chlorates, haloacetic acids (HAAs), and trihalomethanes (THMs). Chlorine (25 mg L −1 free chlorine) and different pH regulators were added to adjust the pH to 5.5 in lettuce wash water. The pH regulators tested neither affected the antimicrobial activity measured as the total mesophilic aerobic bacteria (0.32 log cfu 100 mL −1 ) nor the accumulation of chlorates (28 mg L −1 ), as mean values reached. However, pH regulators significantly affected the formation of chlorine halogenated DBPs. Citric acid, as the pH regulator most widely used in some sectors of the food industry, promoted the highest accumulation of THMs (710 μg L −1 ), although the lowest HAAs (618 mg L −1 ) at the maximum content of organic matter (600–700 mg L −1 ). Among the pH regulators, phosphoric acid was identified as the best pH regulator for chlorine-based sanitizers because of the wide range of pH to generate HOCl (as compared to carbonic acid), its inorganic nature avoiding THM formation (as compared to citric acid), and less corrosive action to industrial equipment (as compared to sulfuric acid). Highlights: Citric acid was the only pH regulator that generated gaseous chlorine at pH < 4.5. All pH regulators influenced halogenated DBPs in chlorinated lettuce wash water but not chlorate. Citric acid promoted the highest content of trihalomethanes and the lowest haloacetic acids. Phosphoric acid limited THM formation and provided a wide range of pH (3.0–6.0) for the maximum % of HOCL.